Phenolic Compounds - Biological Activity 2017
DOI: 10.5772/67232
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of Phenolic Compounds Against Cancers

Abstract: Phenolic compounds are the biggest group of phytochemicals, and many of them have been found in plant-based foods. Polyphenol-rich diets have been linked to many health beneits including cancer. The potential anti-carcinogenic mechanisms of action that have been so far identiied for phenolic compounds, as well as the feasibility reports occurred in vivo. In general terms, under the oxidative stress, polyphenols could act in those cellular mechanisms by participating in the modulation of the redox status and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 81 publications
2
38
0
Order By: Relevance
“…However, the research conducted by the authors found that LC-SS has a significant inhibition effect on NF-κB (p = 0.046), although NF-κB expression in LC-SS is significantly lower than that in BHCl (p = 0.000). 22 This indicates that LC-SS affects NF-κB expression and activity in cells other than macrophages such as monocytes, dendritic cells, mast cells, and T lymphocytes. 23 Besides affecting macrophages, phenolic compounds in LC-SS utilize several potential pathways to inhibit NF-κB by THP-1-activated human monocytes, the degradation of IκBα in human mast cells and also directly impede dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the research conducted by the authors found that LC-SS has a significant inhibition effect on NF-κB (p = 0.046), although NF-κB expression in LC-SS is significantly lower than that in BHCl (p = 0.000). 22 This indicates that LC-SS affects NF-κB expression and activity in cells other than macrophages such as monocytes, dendritic cells, mast cells, and T lymphocytes. 23 Besides affecting macrophages, phenolic compounds in LC-SS utilize several potential pathways to inhibit NF-κB by THP-1-activated human monocytes, the degradation of IκBα in human mast cells and also directly impede dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds and terpenoids possess the ability to prevent tumor cell progression by different antitumor mechanisms [ 16 , 43 ]. Generally, these compounds can modulate the redox status and act on cellular processes such as cell proliferation, differentiation, inflammation, apoptosis, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The methanol extract of cactus roots has been used to study the effect on ethanol-induced ulcers in rats [61]. The methanolic root extract of O. ficus-indica has a high total phenolic content and results in high anti-oxidant activity by inactivating genotoxic molecules such as reactive oxygen species [111]. Rats treated with 80% ethanol showed an increase in the size of the gastric lesion in the stomach, and when the rats were treated with the methanol extract of the root at concentrations of 200 mg/kg, 400 mg/kg, and 800 mg/kg, showed a reduction in the ulcer lesion by 49.21%, 83.13%, and 92.59%, respectively.…”
Section: Anti-cancer and Anti-tumor Activitymentioning
confidence: 99%